ALTERNATIVE LUBRICATING OILS - A. F. Khuzhakulov; K. Sh. Khotamov (Journals Park Publishing, 2023)
This paper presents the results of a study of alternative lubricating oils. To solve the problems of preventing environmental pollution and import-substituting alternative fuels and lubricants based on local raw materials with the involvement of additives of plant origin.
Keywords: mineral oils, waste oils, raw materials, additive, impurities, vegetable oils, chemical analysis, temperature biofuel, biodegradability.